2020
DOI: 10.3400/avd.oa.20-00024
|View full text |Cite
|
Sign up to set email alerts
|

Grip Exercise of Non-Paretic Hand Can Improve Venous Return in the Paretic Arm in Stroke Patients: An Experimental Study in the Supine and Sitting Positions

Abstract: This study aims to determine the effect of grip exercise by the non-paretic hand on venous return in the paretic arm in stroke in sitting and supine positions. Methods: The study population included 21 stroke patients (mean age, 59.5 years). The diameter (mm) and time-averaged mean velocity (TAMV) (cm/s) of the axillary vein on the paretic side were measured by ultrasound during three distinct conditions: resting, rhythmic non-resistive grip exercise, and resistive exercise (30% of maximum grip strength) in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…strength deficit. Grip exercise by the non-paretic hand was found to be effective in increasing the venous flow volume in the paretic hand, in accordance with the literature ( Hayashi and Abe, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…strength deficit. Grip exercise by the non-paretic hand was found to be effective in increasing the venous flow volume in the paretic hand, in accordance with the literature ( Hayashi and Abe, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that two main factors, muscle and respiratory pumps, are recognized as the peripheral venous return to the heart [ 24 ]. Hand exercises, such as grasping empty fists and gripping hand muscle developer, can increase venous return without the influence of systemic circulation [ 25 ]. As a way of the venous return, simply performing finger movements or acupoint massage may not have a significant intervention effect due to the small degree of muscle contraction.…”
Section: Discussionmentioning
confidence: 99%